The virtues of being peripheral, recreational, and transnational: local wild food and medicinal plant knowledge in selected remote municipalities of Calabria, Southern Italy - Mattalia, Giulia; Corvo, Paolo; Pieroni, Andrea (Ethnobotany Research and Applications, 2020)
Background: The Italian “Strategy for Inner Areas” includes a series of actions to avoid depopulation of rural areas by safeguarding the territory from hydrogeological instability and triggering development. Such strategy classified each municipality according to the distance to a centre defined as a town where certain services are provided. This article analyses the ethnobotanical knowledge in four villages distant from a centre. Moreover, it discusses the effect of a millennium-old sacred natural site (SNS), the Certosa of Serra San Bruno, on the local ethnobotanical knowledge. Methods: Sixty semi-structured interviews were conducted among elderly inhabitants of two peripheral and two ultra-peripheral Calabrian villages in 2017 and 2018. The interviews focused on the use of local wild and semi-wild plants currently gathered, for both culinary and medicinal purposes, and the modes of preparation and consumption. Results: Our study reveals that in Calabria ethnobotanical knowledge is better preserved when it can contribute to household food security in contexts of remoteness and extremely poor economic conditions or when relative well-being allows spending time foraging as a recreational activity. Moreover, we found peculiar ethnobotanical practices in Serra San Bruno which may have been introduced by the monastic community and may have contributed to the creation of a “glocal” ethnobotany by introducing knowledge from other European contexts. Conclusions : In conclusion, the “Strategy for Inner Areas” should target the rich ethnobotanical traditional knowledge still present in Calabria as it may represent a powerful tool for achieving sustainable development of peripheral and ultra-peripheral areas. Keywords: Ethnobotany; Inner Areas; Peripheral; Traditional Ecological Knowledge; Sacred Natural Sites